Pengaruh Therapeutic Touch terhadap Penurunan Tekanan Darah Lansia dengan Hipertensi - Heni Purnama Sari; Nafolion Nur Rahmat; Ainul Yaqin Salam (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
High blood pressure, marked by a sustained rise in arterial pressure, poses a complex medical challenge with diverse origins. Internal factors like gender, age, and heredity, combined with external elements such as obesity, unhealthy habits, and stress, contribute to its development. The aging process in elderly individuals often results in reduced adaptive capacity, making them more susceptible to various ailments, including hypertension. To address this issue, Therapeutic Touch is explored as a non-pharmacological intervention, utilizing touch energy to modulate the nervous system and hormonal responses, thereby restoring energy balance and reducing pain and blood pressure levels. This study investigates the impact of Therapeutic Touch on blood pressure reduction in hypertensive elderly individuals in Balung Village, Kendit District, Situbondo Regency, using an experimental design with a one-group pre- and post-test setup. The research involves the entire hypertensive elderly population of Balung Village (32 individuals), with 30 participants selected through purposive sampling for a six-session Therapeutic Touch intervention over two weeks. Data collection employs observation sheets with coded responses, revealing a significant post-intervention shift towards normal blood pressure. Statistical analysis, using the Wilcoxon signed test (p-value: 0.000 ? ? 0.005), supports the acceptance of the hypothesis. In conclusion, Therapeutic Touch proves effective in reducing blood pressure among elderly individuals with hypertension, operating through mechanisms influencing nerves, hormones, and overall body relaxation.